Study on design in an appropriate system to enhance composting process methods - Abd Hamid, Khairul Bariyah; Abu Samah, Mohd Armi; Syed Ismail, Sharifah Norkhadijah; Yunus, Kamaruzzaman (2016)
Composting is one of the biological waste treatment options to treat the increasing amount of food waste-However, depending on the food waste composition, the duration for the compost to reach it completion stage can be very long. This research will focus on improving waste *uoug"*"rri system by enhancing composting process methods. The food waste collected will b" g.irding beiore puiit i.rto the composting bin. The composting bin will be installed with a rotator. The compost will be turned every 15 minutes for 24 hours' The physicochemical analysis will be done before and after the compost turned and microbial analysis will be done every day. The improve methods will save time and cost for composting process and produce higtrqua-lity fertilizer. Quality of soil texture also increases. Besides that, the new system to *urug" organic waste mainly food waste can be recommend. The proposed method will orr"."i*" ivaste problem and strengthen also solve an existing waste management system. It also improving and provide better environment for future generation. The policy and action plan for waste management in Malaysia also can be improve and strengthen.